Noise disturbance caused by outdoor activities- a simulated-environment study for Ali Sami Yen Stadium, A°stanbul - Dal, Zeynep; Akdag, Nese Yugruk (SPRINGER, 2011)
Negative effects of noise on individuals, the inevitable result of urbanization, have become a significant urban problem in our day. Introduction of an approach to the noise problem on an urban-planning scale lightens the burden of measures required to be taken against noise at the stages of regional and developmental planning. Stadiums, which should be also evaluated from the point of noise problem when planning decisions are made on the urban planning scale, may cause very serious problems differing depending on the region they are located in. In this article, various dimensions of the noise problem caused by stadiums have been exemplified by making an assessment on Ali Sami Yen football stadium located in Mecidiyekoy district which is among important residential and commercial centres of A degrees stanbul or Turkey. When the simulation results obtained for ordinary days and match days are evaluated, it has been found out that the people living in the area are exposed to noise levels substantially exceeding the acceptable values. Results of the survey conducted in the area have clearly revealed the existence of noise problem, too.
Keywords: Noise pollution; Noise mapping; Stadium noise; Ali Sami Yen Stadium; EXPOSURE; Environmental Sciences & Ecology